2022
DOI: 10.1055/a-1727-6309
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C Concentration During the First Three Postnatal Days in Healthy Term Newborns

Abstract: Objective Cystatin C (Cys-C) concentration has not been examined sufficiently among healthy newborn population, particularly in terms of reference values. This study aimed to establish gender-, postnatal age- and birth weight-specific Cys-C concentration for healthy term newborns. Its objective was also to examine if there were any differences between our measured concentration and the reference interval establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In a study of 50 term and 58 preterm neonates, Harmoinen et al 17 reported a reference interval of 1.34-2.57 mg/L and 1.36-2.23 mg/L, respectively, for the preterm and the term neonates. In a study of 90 term neonates, Mikulic et al 18 reported a reference interval of 0.93-3.15 mg/L and 1.5-3.36 mg/L, respectively, for girls and boys. Tong et al 19 investigated gestational and age-specific Cys-C reference intervals in 1044 neonates, and the reference intervals were generally within the range of 1.3-2.3 mg/L for the neonates whose gestational age was older than 28 weeks.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 50 term and 58 preterm neonates, Harmoinen et al 17 reported a reference interval of 1.34-2.57 mg/L and 1.36-2.23 mg/L, respectively, for the preterm and the term neonates. In a study of 90 term neonates, Mikulic et al 18 reported a reference interval of 0.93-3.15 mg/L and 1.5-3.36 mg/L, respectively, for girls and boys. Tong et al 19 investigated gestational and age-specific Cys-C reference intervals in 1044 neonates, and the reference intervals were generally within the range of 1.3-2.3 mg/L for the neonates whose gestational age was older than 28 weeks.…”
Section: Disscussionmentioning
confidence: 99%
“…16 Neonatal serum Cys-C originates almost exclusively in the neonate, making it a promising alternative to SCr for evaluating renal function in neonates. Currently, the reference interval of serum Cys-C in neonates have only been reported in a few small studies, [17][18][19] and the reference change value (RCV) of serum Cys-C in neonates have not been investigated.…”
Section: Introductionmentioning
confidence: 99%